KOMPOSISI DAN DISTRBUSI MOLUSKA DI DATARAN KARANG CAGAR ALAM LEUWEUNG SANCANG, JAWA BARAT - AHMAD JAUHAR ARIEF (BERITA BIOLOGI, 1987)
AHMAD JAUHAR ARIEF. 1987.The composition and distribution of coral-reef molluscs community in Leuweung Sancang Reserve, West Java,Berita Biologi,3(7): 310 - 316.Observation was made on the moluscan fauna of coral-reef area at Leuweung Sancang Rcseive, West Java.All together,43 species of molluscs,representing three classes were collected The study mostly concern with the composition and distribution of these groups of animal.The analysis suggest that type of substrats is one of the major factors influencing the life habit of mollusc.The relationship between two aspects with the life habit and habitat is discussed.